Developing sustainable food systems, policies, and securities - Obayelu, Abiodun Elijah, 1972-; Obayelu, Oluwakemi Adeola, 1974- (Practice, progress, and proficiency in sustainability (PPPS) book series., 2020)
"This book provides multidisciplinary perspectives on how to develop sustainable food systems, policies, and securities"--Provided by publisher".